2023
DOI: 10.3390/ijms24065463
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Extracellular Matrix in Endometrial and Cervical Cancer: A Systematic Review

Abstract: Endometrial and cervical cancers are the two most common gynaecological malignancies and among the leading causes of death worldwide. The extracellular matrix (ECM) is an important component of the cellular microenvironment and plays an important role in developing and regulating normal tissues and homeostasis. The pathological dynamics of the ECM contribute to several different processes such as endometriosis, infertility, cancer, and metastasis. Identifying changes in components of ECM is crucial for underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In addition to Col IV and laminin, fibronectin is a major component of the endometrial cancer tumor microenvironment and has been previously demonstrated to promote endometrial cancer growth and invasion. 1,17,35 We evaluated fibronectin from 0.125 to 0.175 mg/mL and found that the concentration that maximized endothelial and endometrial cancer metastatic behavrior was 0.17 mg/mL, at the higher end of our tested range. All three of these ECM components had significant interactions with each other as well as ECM components in the bottom hydrogel, again highlighting the importance of capturing the layered architecture and multicellular nature of the endometrial cancer tumor microenvironment.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to Col IV and laminin, fibronectin is a major component of the endometrial cancer tumor microenvironment and has been previously demonstrated to promote endometrial cancer growth and invasion. 1,17,35 We evaluated fibronectin from 0.125 to 0.175 mg/mL and found that the concentration that maximized endothelial and endometrial cancer metastatic behavrior was 0.17 mg/mL, at the higher end of our tested range. All three of these ECM components had significant interactions with each other as well as ECM components in the bottom hydrogel, again highlighting the importance of capturing the layered architecture and multicellular nature of the endometrial cancer tumor microenvironment.…”
Section: Discussionmentioning
confidence: 94%
“…Endometrial cancer, the most common gynecological cancer in developed countries and the sixth most common type of cancer worldwide, presents a significant healthcare challenge. 1,2 In 2023, 66,200 women were diagnosed with this disease and over 13,000 women died from endometrial cancer in the United States alone. 3 While early-stage endometrial cancer can be effectively treated with surgery, chemotherapy, and radiation, advanced stages often have poor prognoses, with a five year survival rate under 20%, primarily due to metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…The main proteins involved in cell invasion are MMPs, found in the ECM, and cadherins found at the cell membrane [ 253 ]. Specifically, MMPs degrade ECM proteins, while changes in cadherins expression levels contribute to the EMT, also important to start the cell’s invasion process [ 254 ]. The FAP is also fundamental for cell survival thanks to the presence of multiple protein kinases, such as Akt, mTOR, PI3K and MAPKs, that start pro-survival signaling cascades [ 255 ].…”
Section: Discussionmentioning
confidence: 99%
“…89 The Extracellular matrix degradation play also an important role the pathogenesis of endometriosis. 90 Singh et al developed a dual drug-loaded PLGA NPs that combines the anti-angiogenic and antioxidant properties of epigallocatechin gallate (EGCG) and the matrix metalloproteinase inhibitory activity of antibiotic doxycycline (Dox) 91 in order to improve and reduce the limitations when they are used in their native forms. The novelty of this nanosystem is given by the delivery of two different agents (Dox and EGCG) in a single vehicle: the dual agent-NPs was more efficient at reducing levels of metalloproteinase (MMPs) and angiogenic factors in mice with endometriosis than single drug-loaded NPs.…”
Section: Emerging Therapeutic and Theranostic Nanotechnology Approach...mentioning
confidence: 99%